Study of Adsorption and Desorption on Gold Metals by Biomass Saccharomyces cerevisiae. Thermodynamic Review - Masruroh Masruroh; Lailatin Nuriyah; Siti Jazimah Iswarin; Eka Rahmawati (Natural B, Journal of Health and Environmental Sciences, 2011)
A Study on biosorption of gold solution (Au) by Saccharomyces cerevisiae has been caried out. These studies included determination of optimum pH, optimum Au solution concentration,  isotherm and biosorption capacity based on termodinamycs theory, and mechanims of interaction between Au ion and Saccharomyces cerevisiae biosorben. Mechanisms of interaction were known with Au ion on Saccharomyces cerevisiae biosorben using aquadest and 1 M HCl. The result showed that the optimum adsorption process of Au solution by Saccharomyces cerevisiae biosorben took place on pH 5, adsorbat concetration of 100 mg/L was 2.2321 mg/g of yeast. The adsorption isoterm followed the Langmuir adsorption with regresion value of 0.8550 (R2= 0.8550), that indicates that the chemisorption process occurred on the first monolayer on the adsorbent surface. From the thermodynamics theory gives Gibbs free energy of the process a value of ΔG = -0.09195 kJ/mol and showing spontaneous physisorption process. The number of Au ion desorption by using HCL was 73.98%, whereas by using aquades it was 35.42%. It indicated that the main interaction between Saccharomyces cerevisiae biosorben and Au ion was chemisorption.